Lin41/Trim71 is essential for mouse development and specifically expressed in postnatal ependymal cells of the brain - Cuevas, Elisa; Rybak-Wolf, Agnieszka; Rohde, Anna M.; Nguyen, Duong T. T.; Wulczyn, F. Gregory (Frontiers in Cell and Developmental Biology, 2015)
Lin41/Trim71 is a heterochronic gene encoding a member of the Trim-NHL protein family, and is the original, genetically defined target of the microRNA let-7 in C. elegans. Both the LIN41 protein and multiple regulatory microRNA binding sites in the 3′ UTR of the mRNA are highly conserved from nematodes to humans. Functional studies have described essential roles for mouse LIN41 in embryonic stem cells, cellular reprogramming and the timing of embryonic neurogenesis. We have used a new gene trap mouse line deficient in Lin41 to characterize Lin41 expression during embryonic development and in the postnatal central nervous system (CNS). In the embryo, Lin41 is required for embryonic viability and neural tube closure. Nevertheless, neurosphere assays suggest that Lin41 is not required for adult neurogenesis. Instead, we show that Lin41 promoter activity and protein expression in the postnatal CNS is restricted to ependymal cells lining the walls of the four ventricles. We use ependymal cell culture to confirm reestablishment of Lin41 expression during differentiation of ependymal progenitors to post-mitotic cells possessing motile cilia. Our results reveal that terminally differentiated ependymal cells express Lin41, a gene to date associated with self-renewing stem cells.